Methodological approach to create an atlas using a commercial auto‐contouring software. Issue 12 (25th November 2020) - Casati, Marta; Piffer, Stefano; Calusi, Silvia; Marrazzo, Livia; Simontacchi, Gabriele; Di Cataldo, Vanessa; Greto, Daniela; Desideri, Isacco; Vernaleone, Marco; Francolini, Giulio; Livi, Lorenzo; Pallotta, Stefania
Abstract: Purpose: The aim of this work was to establish a methodological approach for creation and optimization of an atlas for auto‐contouring, using the commercial software MIM MAESTRO (MIM Software Inc. Cleveland OH). Methods: A computed tomography (CT) male pelvis atlas was created and optimized to evaluate how different tools and options impact on the accuracy of automatic segmentation. Pelvic lymph nodes (PLN), rectum, bladder, and femurs of 55 subjects were reviewed for consistency by a senior consultant radiation oncologist with 15 yr of experience. Several atlas and workflow options were tuned to optimize the accuracy of auto‐contours. The deformable image registration (DIR), the finalization method, the k number of atlas best matching subjects, and several post‐processing options were studied. To test our atlas performances, automatic and reference manual contours of 20 test subjects were statistically compared based on dice similarity coefficient (DSC) and mean distance to agreement (MDA) indices. The effect of field of view (FOV) reduction on auto‐contouring time was also investigated. Results: With the optimized atlas and workflow, DSC and MDA median values of bladder, rectum, PLN, and femurs were 0.91 and 1.6 mm, 0.85 and 1.6 mm, 0.85 and 1.8 mm, and 0.96 and 0.5 mm, respectively. Auto‐contouring time was more than halved by strictly cropping the FOV of the subject to be contoured to the pelvic region. Conclusion: A statistically significant improvement of auto‐contours accuracy was obtained using our atlas and optimized workflow instead of the MIM Software pelvic atlas.